Improving Teacher’s Performance Quality in The Freedom to Learn Program Using Zone-Based Lesson Study by Exchanging Teachers - Kristiani, Ninik (Universitas Negeri Makassar, 2020)
This study aims to investigate the implementation of the strategy of zone-based lesson study by exchanging teachers in order to improve teacher performance, including (1) designing RPPs in accordance with the Circular Letter (SE) of the Indonesian Ministry of Education and Culture (Mendikbud) No. 14 of 2019 concerning the Simplification of RPPs (lesson plans); (2) designing teaching materials such as UKBM (Self-Study Activity Unit) and LKPD (Student Worksheet); (3) implementing Freedom to Learn (FTL); and (4) increasing student participation during FTL. Besides, the strategy can also prepare teachers to become zone organizer teachers. Data were collected for two cycles in which each cycle had two meetings. Data were analyzed through reduction, interpretation, inferences, follow-up, and conclusion. The research subjects were the best quality teachers in their subjects: 1 Biology teacher and 1 History teacher from three schools in cycle 1; and 1 Math teacher and 1 Sociology teacher from two schools in cycle 2. The number of schools where treatments were given in cycle 2 was reduced to follow SK (decree) issued at the end of cycle 1, stating that one of the schools is beyond the target school area. Results showed that the strategy of zone-based lesson study by exchanging teachers can facilitate the improvement of teacher’s performance quality, the path for teachers to become zone organizers, and the work production for professional development as a result of collaboration between supervisors, principals, and teachers